Pseudolaguvia viriosa, a new catfish (Teleostei: Sisoridae) from north-eastern India - Ng, Heok Hee; Tamang, Lakpa (Zootaxa, 2012)
This study describes Pseudolaguvia viriosa, a new miniature sisorid catfish from the Brahmaputra River drainage in Ar-unachal Pradesh, northeastern India. Pseudolaguvia viriosa can be distinguished from congeners in having a combinationof: eye diameter 10–15% HL, interorbital distance 35–38% HL, head width 21.5–23.5% SL, thoracic adhesive apparatusreaching beyond base of last pectoral-fin ray, pectoral spine length 26.9–32.9% SL, dorsal spine length 23.4–29.0% SL,dorsal spine with anterior edge smooth or with rugose surface only on distal third of spine, body depth at anus 16.9–19.0%SL, length of adipose-fin base 12.5–15.4% SL, caudal peduncle length 14.8–17.7% SL, caudal peduncle depth 7.4–9.8% SL, caudal-fin length 26.5–32.4% SL, 28–29 vertebrae, and one or more distinct pale bands encircling body.